The impact of COVID-19 pandemic on decreasing hospitalization rates and management of acute coronary syndrome: a study from single centre hospital in Yogyakarta, Indonesia - Hendry Purnasidha Bagaswoto; Ferdinandus Bayu Satria; Hani Khairina; Nahar Taufik; Budi Yuli Setianto (Universitas Gadjah Mada, 2023)
The Corona virus disease-2019 (COVID-19) pandemic has an impact on the medical field, one of which is service for patients with acute coronary syndrome (ACS). Studies in other countries showed a sudden decrease in admission rates, and percutaneous coronary intervention (PCI), one of ACS treatments, has an impact due to this pandemic. This study aimed to ascertain the effect of COVID-19 on the admissions and management of patients with ACS in Yogyakarta, Indonesia. It was an observational single center study conducted by collecting data for ACS patients at Dr. Sardjito General Hospital, Yogyakarta. Admission data for March 2019 to February 2020 were pre pandemic data, while those gathered from March to December 2020 were pandemic data. Data from 864 (pre pandemic period) and 338 patients (during the pandemic period) were further analyzed. The results showed a decrease in ACS patients’ admission during the pandemic. The most remarkable reduction occurred in those with ST-segment elevation myocardial infarction (STEMI), followed by non-STEMI (NSTEMI) and unstable angina pectoris (UAP) (63.4, 61.4, and 40.9%, respectively). Furthermore, the PCI procedure decreased compared to the period before the pandemic. No significant differences in patients’ characteristics was observed (p>0.05), except for the incidence of pneumonia (p <0.001). Finally, the mortality rate was higher during the pandemic than before (14.8 vs 13.2%), although it was not significant (p>0.05). This study showed that COVID-19 caused a sensible reduction in the admission rates for ACS patients and the number of PCI procedures have been performed. On the other hand, their mortality rate did not increase significantly. However, it is essential to improve healthcare services for ACS patients considering the uncertainty of ending the COVID-19 outbreak.